2019
DOI: 10.3390/su11226451
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Evaporative Cooler to Reduce Energy Consumption and Improve Thermal Comfort in Free-Running Spaces

Abstract: The need to reduce energy consumption in buildings is imperative, but we must maintain individual thermal comfort of the occupants to ensure their well-being and productivity. Personal conditioning systems (PCS) have been suggested as a strategy to achieve both energy efficiency and thermal comfort, as they are considered to be low-energy consumers, allow increasing set-point temperatures, and give occupants the chance to control their own personal environment. While most warm-environment PCS are based on air-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…There are several some other methods for evaporative cooling such as spray passive Downdraft evaporative cooling (PDEC) which has been intensively investigated such as the work of Kang [46]. In a study conducted by Ana [47] highlighted that use of evaporative cooling systems can achieve thermal comfort level with a free running operation system in the climate of Spain. This study used wide range of tools to conduct the study, Table 2 indicates equipment used.…”
Section: Evaporative Cooling In Buildingsmentioning
confidence: 99%
“…There are several some other methods for evaporative cooling such as spray passive Downdraft evaporative cooling (PDEC) which has been intensively investigated such as the work of Kang [46]. In a study conducted by Ana [47] highlighted that use of evaporative cooling systems can achieve thermal comfort level with a free running operation system in the climate of Spain. This study used wide range of tools to conduct the study, Table 2 indicates equipment used.…”
Section: Evaporative Cooling In Buildingsmentioning
confidence: 99%
“…In addition to a variety of fans that enhance airflow, numerous new devices for lowering the supply air temperature, such as evaporative cooling devices, have been introduced [52]. Tejero-González et al [53] demonstrated that evaporative cooling devices can substantially improve thermal comfort in open office spaces. These devices are low-power, easy-to-use, and efficiently ensure human thermal comfort under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…717 Some researchers have recently conducted theoretical and experimental studies on these new hybrid DEC and IDEC applications. 1828…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] Some researchers have recently conducted theoretical and experimental studies on these new hybrid DEC and IDEC applications. [18][19][20][21][22][23][24][25][26][27][28] Rong et al 29 have experimentally investigated the dynamic behavior of cellulose pads, including cooling efficiency and dry-bulb air temperature drop, water consumption under the influence of parameters such as different air velocities, different dynamic circulation rates (due to the varying lengths of on and off operation periods of the pump). They used 21 different time patterns for the periodic operation of the pump at different air velocities.…”
Section: Introductionmentioning
confidence: 99%